Study of Diversity of Scolopendrid Centipedes (Chilopoda: Scolopendromorpha) in Achalpur Region, District Amravati, Maharashtra, India - Ahsan, Mohammad Misbahul; Danish, Syed; Kondulkar, S.R. (International Journal of Scientific Research in Biological Sciences, 2023)
The present paper deals with the diversity of Scolopendrid Centipedes fauna in Achalpur region, District Amravati, Maharashtra State of India. This study was done during July 2021 to October 2021 for total four months by visiting different habitats of Achalpur region. Samples were collected by using different collection methods such as hand collection method by using forceps and species were identified with the help of standard taxonomic literature. Total 04 species of Centipedes belongings to 02 genera namely Scolopendra and Cormocephalus under family Scolopendridae were identified from the study area.